(untitled) (Stato, Chiese e pluralismo confessionale, 2025)
Emergencies can affect everybody in a given territory, but vulnerable groups are exposed to greater risks than the rest of the population. This contribution looks at the UN perspective concerning a specific vulnerable category, that is, religious minorities, in states of emergencies, by focusing on the Emergency Special Sessions of the General Assembly and on the Human Rights Council’s Special Procedures.